2000
DOI: 10.1302/0301-620x.82b5.9888
|View full text |Cite
|
Sign up to set email alerts
|

Expression of growth factors, cytokines and matrix metalloproteinases in frozen shoulder

Abstract: F rozen shoulder is a chronic fibrosing condition of the capsule of the joint. The predominant cells involved are fibroblasts and myofibroblasts which lay down a dense matrix of type-I and type-III collagen within the capsule. This subsequently contracts leading to the typical features of pain and stiffness. Cytokines and growth factors regulate the growth and function of the fibroblasts of connective tissue and remodelling of the matrix is controlled by the matrix metalloproteinases (MMPs) and their inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
122
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(135 citation statements)
references
References 15 publications
9
122
2
2
Order By: Relevance
“…The chronic fibrosis process of capsulitis is confirmed by observing the histologic presentation of fibroblast cell proliferation. Matrix metalloproteinase and fibrogenic growth factors are also increased in adhesive capsulitis patients15.…”
Section: Discussionmentioning
confidence: 99%
“…The chronic fibrosis process of capsulitis is confirmed by observing the histologic presentation of fibroblast cell proliferation. Matrix metalloproteinase and fibrogenic growth factors are also increased in adhesive capsulitis patients15.…”
Section: Discussionmentioning
confidence: 99%
“…All non-operative interventions are costed in the NHS tariff for Scotland therefore giving a nominal cost for each physiotherapy session and steroid injection [8]. Government data also supplies the mean cost of one day of absence from work [9].…”
Section: Resultsmentioning
confidence: 99%
“…A previous study showed that frozen shoulder can be induced by administration of synthetic TIMPs, suggesting that a decrease in the MMP/TIMP ratio affects collagen turnover (Hutchinson et al, 1998). Additionally, capsular tissues from frozen shoulder patients were found to show upregulated levels of MMP and natural TIMP mRNA (Bunker et al, 2000). Thus, limiting the amount and the function of MMPs may reduce connective tissue matrix degradation and thus limit synovial fibrosis progression.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous studies demonstrated that the elasticity of the joint capsule decreased in an adhesive capsulitis model and the range of motion became normal after capsular release (Hagiwara et al, 2006;Chimoto et al, 2007). Growth factors such as transforming growth factor-beta (TGF-b), platelet-derived growth factor, and hepatocyte growth factor are also involved in frozen shoulder (Rodeo et al, 1997;Bunker et al, 2000). Matrix metalloproteinases (MMPs) may play an important role in the pathogenesis of frozen shoulder (Bunker et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation